2012
DOI: 10.1038/hr.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of endothelium-derived hyperpolarizing factor compensates for the loss of nitric oxide in mesenteric arteries of dahl salt-sensitive hypertensive rats

Abstract: This study was designed to determine whether a high-salt diet would alter endothelial function and, if so, the relative contributions of endothelium-derived hyperpolarizing factor (EDHF) and nitric oxide (NO) to any changes in vasomotor responses. Male Dahl salt-sensitive (DS) rats were given either a high-salt diet (8% NaCl, DS-H) or a low-salt diet (0.4% NaCl, DS-L) for 6 weeks. Membrane potentials and contractile responses were recorded from the isolated superior mesenteric arteries. After salt loading, DS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…The vascular strain governed by smooth muscle cells in the small arteries plays important roles in the formation and elevation of BP [19]. Most previous studies that explored vascular function were performed in vitro and mainly used isolated aortas or distributing arteries [20, 21]. However, the main artery and the distributing arteries play a much smaller role in maintaining peripheral vascular resistance when compared with the small arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular strain governed by smooth muscle cells in the small arteries plays important roles in the formation and elevation of BP [19]. Most previous studies that explored vascular function were performed in vitro and mainly used isolated aortas or distributing arteries [20, 21]. However, the main artery and the distributing arteries play a much smaller role in maintaining peripheral vascular resistance when compared with the small arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In coronary artery disease, compensation occurs via increased K ϩ channel activity and increased release of hyperpolarizing factors (30), while in hypercholesterolemia, compensatory increases in Ca 2ϩ -dependent K ϩ channels is evident (31). EDHF has also been shown to compensate for diminished nitric oxide-dependent dilation in numerous disease states, including type 2 diabetes (36), hypertension (14), and hyperparathyroidism (45).…”
Section: Discussionmentioning
confidence: 99%
“…A primary feature of endothelial dysfunction is the inability of arteries and arterioles to dilate fully in response to vasoactive agonists (11). However, other vasodilatory pathways have been shown to be augmented in conditions in which nitric oxide availability is reduced (3,14,30,36). This redundancy in vasodilator signaling pathways allows for compensation if one mechanism is impaired.…”
mentioning
confidence: 99%
“…Considering that the L -NA-resistant vasorelaxation to ACh seemed to be subtly augmented while the response to SNP was unaffected under hypoxia for 3 h, endothelium-derived relaxing factors other than NO, such as prostacyclin and endothelium-derived hyperpolarizing factor, may compensate for the decrease in endothelial NO bioavailability. In fact, accumulating evidence has shown that these mediators act as backup mechanism to preserve endothelium-derived vasodilator regulation of mesenteric arterial tone in several disease models, including hypertension [21,22] and diabetes [23]. Unfortunately, there is no evidence that this phenomenon quickly occurs within hours when the bioavailability of NO is impaired, so further study is required to establish this indication.…”
Section: Discussionmentioning
confidence: 99%